2020
DOI: 10.1007/s11818-020-00254-9
|View full text |Cite
|
Sign up to set email alerts
|

Interest in telephone nightmare counselling in patients with sleep-related breathing disorders

Abstract: Background and objective Nightmares are typically underdiagnosed and undertreated, even though frequent nightmares are quite common in patients with sleep-related breathing disorders. Based on a previous study, we investigated whether patients would respond if they were specifically asked whether they would be interested in telephone counselling about nightmares and nightmare treatment. Materials and methods The present study included 537 patients with sleep-related breathing disorders who completed a nightm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The most obvious factor affecting considering seeking professional help for nightmares is nightmare frequency and—if measured explicitly with a global rating scale—nightmare distress, this was found in the present sample and reported in the literature (Belicki, 1992; Schredl et al, 2016; Schredl et al, 2020). The strong association (large effect size) between nightmare frequency and the “having a problem with nightmares” item in the present sample corroborates this argument.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The most obvious factor affecting considering seeking professional help for nightmares is nightmare frequency and—if measured explicitly with a global rating scale—nightmare distress, this was found in the present sample and reported in the literature (Belicki, 1992; Schredl et al, 2016; Schredl et al, 2020). The strong association (large effect size) between nightmare frequency and the “having a problem with nightmares” item in the present sample corroborates this argument.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, it seems important to find new ways to provide adequate and easily accessible treatment options for those persons (Nadorff et al, 2015). Schredl et al (2016) and Schredl et al (2020) offered patients undergoing diagnostic procedures in a sleep laboratory (most often sleep‐related breathing disorders) a telephone counselling session for nightmares, and a substantial number of persons who were affected by nightmares (in addition to their primary sleep disorder, the reason they were administered to the sleep diagnostics) were interested, including many who had never sought professional help before. These findings indicate that actively approaching possible nightmare sufferers can decrease the gap between having the diagnosis and getting treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two participants of the sleep lab group felt uncomfortable talking about private topics on the phone and therefore decided to cease participation [10][11][12][13]. However, previous studies indicated that when directly offered help, 15.5 up to 46.8% of people with frequent nightmares (once a week or more often) expressed their interest in telephone counseling covering information on the etiology and treatment of nightmares [13,14]. Therefore, low-threshold interventions are urgently needed.…”
mentioning
confidence: 99%